Geopolitical Conditions and Election Security in Nigeria - Abang, Sunday Owen; Ademiluyi, Israel Ajewole (Acta Universitatis Danubius. Administratio, 2024)
In the sixty-two years of Nigeria’s existence as an independent nation, a look at the political structure reveals that the core North, comprising North-east, North-west and North-central, has been at the helm of affairs in the presidency for forty-two years, either as military or civilian president. The southern part, made up of South-south, South-west, and South-east have shared the remaining twenty years. The balancing in the South too is greatly in favour of the South-west, followed by the South-south, at the expense of the South-east. This political reality generates tension in the polity, with various ethnic nationalities calling for secession, including the “shortchanged” South-east. It is undeniable that these political turmoils take a toll on the economy and security of the country. This paper set out to examine the geopolitical conditions in Nigeria, with emphasis on the election process, a democratic process that births the regimes, within the context of democratic liberalism. It is a given that elections have turned to violent processes through which governments in power perpetuate themselves, or coerce the voting public into giving way for the success of a choice candidate. This paper adopts secondary method of data collection and interviews. It reveals that securing election in Nigeria is not an easy exercise to achieve in some volatile states. The results of this scientific research recommend the introduction of Electoral Task Force as a panacea to election crises, to be deployed to the polling and collation centres to combat security challenges in the course of elections.